THE MOBILE SPACE AND MOBILE TARGETING ENVIRONMENT FOR INTERNET USERS: FEATURES OF MODEL SUBMISSION AND USING IN EDUCATION - Bykov, В.Ю. (Journal of Information Technologies in Education (ITE), 2014)
Article submitted the results of the analysis of the use of mobile devices in education. The substantiation of the definition of user mobility in the Internet space, taking into account the variability of mobile devices and communications. The use of mobile devices in the educational process is based on the paradigm of open and equal access to quality education. Considered the technology of using different types of devices and their functions . The conditions of user mobility in the internet environment, the factors influencing it, the creation and storage of mobile communications resources . Provided with basic mathematical model of user behavior in a virtual network. A model of migration as a user from device to device , and its geographic move , and then use the resulting model for the design of distance learning systems . Preliminary forecasts have been made on the development of education in the transition from the remote technology to open. It is assumed the appearance of new types of personal devices that will combine the power of a desktop PC and the autonomy of smartphones with constant access for broadband wireless connection to the Internet. The use of cloud technology to store and process information resources training helps centralize and synchronize data and access to them from different devices.